PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK KELOKALAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Linda Eka Pradita; Umi Rachmawati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
The development of digital flipbooks based on local wisdom as a medium for learning Indonesian language material aims to improve learning outcomes. The choice of flipbook as a learning medium is due to the characteristics of Indonesian language subjects, the majority of which are text-oriented which can cause learning boredom in students. Flipbooks are seen as innovative and interesting media that can illustrate concrete experiences in academic concepts so that they can give rise to contextual learning. Flipbook was developed using the ADDIE model including five stages, namely 1) analysis; 2) design; 3) development; 4) implementation and 5) evaluation. The subjects are teachers and students, while the object is a digital flipbook as a learning medium. The material used in learning media is Indonesian language material and local wisdom content. The research results show that the development of Flipbook learning media as digital media can have a positive impact on both teachers and students in improving learning outcomes. The aspect of Indonesian language material used in flipbook media has relevance. This can be seen from the compatibility between descriptive text material which is integrated with local cultural wisdom and tourist attractions. Furthermore, procedural text material is integrated with local food and arts and crafts wisdom.Keywords: flipbook, local wisdom, integration, learning